Self-Regulation Successfully Increases Employee Perceiving a Calling at PT United Tractors TBK Jakarta - Lisa Sarinah; Rizki Nurul Nugraha (West Science Information System and Technology, 2024)
This study builds on Burnette’s SOMA model. The research was conducted to test the premise that a growth mindset of work predicts living a calling and to explore the mediating role of self-regulation in the influence of a growth mindset of work on living a calling. The process in Burnett’s SOMA model includes goal setting, goal operation, goal monitoring, and goal achievement. In this theoretical model, a growth mindset as a motivational construct predicts self-regulation. Data analysis uses the PLS method with the help of SmartPLS software. The research was conducted at PT United Tractors Tbk, located at Jl.Raya Bekasi KM 22 Jakarta, for three months. Research results: A growth mindset of work has a positive but insignificant effect on living a calling, with PValues of 0.244. A growth mindset of work positively and significantly affects self-regulation, PValues of 0.000. Self-regulation has a positive and significant effect on living a calling, with PValues of 0.002. It can mediate (full mediation) a growth mindset of work on living a calling on Employees of PT United Tractors Tbk Jakarta.